A Passion for Security: Intervening to Help Software Developers - Weir, Charles; Becker, Ingolf; Blair, Lynne (2021 IEEE/ACM 43rd International Conference on Software Engineering: Software Engineering in Practice (ICSE-SEIP), 2021)
While the techniques to achieve secure, privacy-preserving software are now well understood, evidence shows that many software development teams do not use them: they lack the 'security maturity' to assess security needs and decide on appropriate tools and processes; and they lack the ability to negotiate with product management for the required resources. This paper describes a measuring approach to assess twelve aspects of this security maturity; its use to assess the impact of a lightweight package of workshops designed to increase security maturity; and a novel approach within that package to support developers in resource negotiation. Based on trials in eight organizations, involving over 80 developers, this paper demonstrates that (1) development teams can notably improve their security maturity even in the absence of security specialists; and (2) suitably guided, developers can find effective ways to promote security to product management. Empowering developers to make their own decisions and promote security in this way offers a powerful grassroots approach to improving the security of software worldwide.